Tocilizumab-coated solid lipid nanoparticles loaded with cannabidiol as a novel drug delivery strategy for treating COVID-19: A review - Zielińska, Aleksandra; Eder, Piotr; Karczewski, Jacek; Szalata, Marlena; Hryhorowicz, Szymon; Wielgus, Karolina; Szalata, Milena; Dobrowolska, Agnieszka; Atanasov, Atanas G.; Słomski, Ryszard; Souto, Eliana B. (Frontiers in Immunology, 2023)
Commonly used clinical strategies against coronavirus disease 19 (COVID-19), including the potential role of monoclonal antibodies for site-specific targeted drug delivery, are discussed here. Solid lipid nanoparticles (SLN) tailored with tocilizumab (TCZ) and loading cannabidiol (CBD) are proposed for the treatment of COVID-19 by oral route. TCZ, as a humanized IgG1 monoclonal antibody and an interleukin-6 (IL-6) receptor agonist, can attenuate cytokine storm in patients infected with SARS-CoV-2. CBD (an anti-inflammatory cannabinoid and TCZ agonist) alleviates anxiety, schizophrenia, and depression. CBD, obtained from Cannabis sativa L., is known to modulate gene expression and inflammation and also shows anti-cancer and anti-inflammatory properties. It has also been recognized to modulate angiotensin-converting enzyme II (ACE2) expression in SARS-CoV-2 target tissues. It has already been proven that immunosuppressive drugs targeting the IL-6 receptor may ameliorate lethal inflammatory responses in COVID-19 patients. TCZ, as an immunosuppressive drug, is mainly used to treat rheumatoid arthritis, although several attempts have been made to use it in the active hyperinflammatory phase of COVID-19, with promising outcomes. TCZ is currently administered intravenously. It this review, we discuss the potential advances on the use of SLN for oral administration of TCZ-tailored CBD-loaded SLN, as an innovative platform for managing SARS-CoV-2 and related infections.